A pilot study on the incorporation of adipose-derived stem cells into bone cements to enhance bone defect regeneration - Julia Lucas-Aparicio; Jatsue Cabrejos-Azama; Jesús Torres; Carmen Rueda; Mohammad-H. Alkhraisat; Luis Blanco-Jerez; Enrique López-Cabarcos (Academia Materials Science)
Advancements in regenerative medicine increasingly focus on developing scaffolds that not only support stem cell proliferation but also guide their differentiation into specific cell types essential for tissue repair. Adipose-derived stem cells (ASCs) are considered a promising option for bone regeneration therapies, primarily because they are readily accessible and can be obtained in large quantities with minimally invasive procedures. This study aims to establish a straightforward and effective novel experimental model for incorporating ASCs into silicon calcium phosphate cement (Si-CPC), potentially enhancing the scaffold’s osteoconductive properties and facilitating bone tissue regeneration. The in vivo evaluation of the cement was carried out using a rabbit model, where titanium cylinders were implanted into pre-drilled slits in the parietal cortical bone. One cylinder served as a control and was filled with Si-CPC alone, while the other received Si-CPC combined with adipose-derived stem cells applied across the surface of the granules. Four weeks after the intervention, histology and histomorphometry tests are performed. In the histology test, the Si-CPC with ASCs presented the training of bony bridges between the material granules. We will need a larger sample to evaluate the amount of new bone formed. However, we can conclude that this new method of incorporating stem cells into bone cements could be a promising tool in bone engineering.